Identification of a novel histone phosphorylation prognostic signature in hepatocellular carcinoma based on bulk and single-cell RNA sequencing - Fan, Lei; Xu, Ling; Tian, Shan; Zheng, Xin (Frontiers in Endocrinology, 2022)
Background: Hepatocellular carcinoma (HCC) is the third leading cause of death in the world, characterized by high morbidity, poor prognosis and high mortality. Histone modifications regulate intracellular gene expression at the post-transcriptional level, and disturbances in the regulatory pattern of histone modifications at individual locus or across the genome can lead to tumorigenesis of HCC. In this study, an assessment of the prediction abilities of a model based on histone phosphorylation genes was conducted in HCC. Methods: Differentially expressed genes were screened using TCGA, ICGC and GEO databases, and a new risk signature was constructed by univariate Cox regression and Lasso regression analysis. Predictive nomograms were established by multivariate Cox regression of risk scores and clinical parameters, calibration curve and decision curve analysis were used to evaluate the models. The ssGSEA methods were used to determine the effect of risk scores on the tumor immune microenvironment. Data for HCC single-cell RNA sequencing (scRNA-seq) have been downloaded from Gene Expression Omnibus (GEO) to understand the role of histone phosphorylation genes in tumorigenesis. Results: Our analyses of nine histone phosphorylation-related genes provided prognostic insights. Overall survival in the low-risk and high-risk groups was statistically higher, respectively (P<0.001). Cox regression analysis revealed that the risk score is a significant predictor of HCC outcomes (HR=2. 2.62, 95%CI: 1.248-5.514, P=0.011). In addition, a nomogram combining risk scores with TNM stages was constructed and tested from calibration curves and decision curves (AUC=0.780). Type-I-IFN Response genes, MHC-class-I genes and Type-II-IFN Response genes were overexpressed in the high-risk group. Conclusion: Histone phosphorylation gene risk score is closely related to the prognosis of HCC, tumor immune process and tumor cell progression.